ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN RISIKO PERUSAHAAN - Mutiara Puspawardani; Agung Juliarto (Diponegoro Journal of Accounting, 2019)
This research aims to get emprical evidence about the factors influencing risk disclosure in example, firm size, industry type, leverage degree,board size and board independent. Agency theory is used to explain the relationship among variables. This research uses purposive sampling in carry out sample selection. There are 188 non-finances firms which is listed in Indeks Kompas 100 in the period 2015-2017is become sample in this research. Risk disclosure in this research was obtained by using content analysis based on the identification of sentence of risk disclosure in the annual report. Statistical method used for hypothesis testing was multiple linear regression. This research finds that firm size, leverage degree, board size and board independent have positive association with firm risk disclosure, whereas industry type does not have significant influence on risk disclosure. However these factors simultaneously influence risk disclosure.